Um teste da paridade descoberta da taxa de juros no Brasil pós - real - Karbel, Marcelo Voloch (2013)
Due to the greater integration of financial markets of the countries the relationship betweeninterest rates and exchange rates had a significant increase in importance and in Brazil theincrease was even greater due to the change of exchange rate regime. The main objective of this study is to test the Uncovered Interest Rates Parity (UIP) in Brazil in the period from October/2008 to January/2000 econometric tests and there was a significant change in economic scenario and to avoid loss of structure the analysis was divided into two periods (January/2000 to April 2003 and Maio/2003 to October/2008). In the first period as there were problems of liquidity in international financial markets and distrust on the part of economic agents on the maintenance of the internal economic policy UIP was not rejected due to the strong dependence on external capital on the financing of domestic and external debt which is evidenced by the strong correlation between interest rates and domestic and foreign in the following period when the recovery was found to improve liquidity and expectations on Brazilian economy, we found evidence that the UIP can not be accepted due to the presence of Brazil in which risk the volatility of international reserves has a great influence and this was added to make the model more complete.